Lineage contribution of the mesendoderm progenitors in the gastrulating mouse embryo - Masamsetti, V. Pragathi; Salehin, Nazmus; Kim, Hani Jieun; Santucci, Nicole; Weatherstone, Megan; McMahon, Riley; Marshall, Lee L.; Knowles, Hilary; Sun, Jane; Studdert, Josh B.; Aryamanesh, Nader; Wang, Ran; et al. (Developmental cell, 2025)
A population of putative mesendoderm progenitors that can contribute cellular descendants to both mesoderm and endoderm lineages is identified in the gastrulating mouse embryo. These progenitor cells are localized to the posterior epiblast, primitive streak, and nascent mesoderm of mid-streak- (E7.0) to late-streak-stage (E7.5) embryos. Lineage tracing in vivo identified that putative mesendoderm progenitors contribute descendants to the definitive endoderm and the axial mesendoderm of E7.75 embryos and to the endoderm of the foregut and hindgut of the E8.5–8.75 embryos. Differentiation of mouse epiblast stem cells identified that the choice between endoderm and mesoderm cell fates depends on the timing of Mixl1 activation upon exit from pluripotency. The knowledge gained on the spatiotemporal distribution of mesendoderm progenitors and the molecular drivers underpinning the divergence of cell lineages in these progenitors enriches our mechanistic understanding of the allocation of the tissue progenitors to germ layer derivatives in early development. [Display omitted] •A population of mesendoderm progenitors is identified in mid-streak E7.0 mouse embryo•These progenitors contribute descendants to mesoderm and endoderm of late-gastrula embryo•Mixl1 activity guides the differentiation to axial mesendoderm and definitive endoderm Masamsetti et al. identified a transient non-renewing cell population that displays dual lineage propensity for mesoderm and endoderm in mouse embryos at mid- to late-gastrulation. These mesendoderm progenitors contribute to the anterior mesendoderm, anterior definitive endoderm, and embryonic gut endoderm.